PENGARUH PENDEKATAN DEEP LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Savira Seviardini; Nanda Faradita, Meirza; Naila, Ishmatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of the Deep Learning approach on students’ critical thinking skills in IPAS learning at the elementary school level. Learning conditions that focus on the lecture method have caused students’ critical thinking skills in understanding IPAS to be underdeveloped, which became the background of this study. The research population included all sixth-grade students in classes VI-A and VI-B, totalling 60 students. This study employed a quantitative quasi-experimental design using a Non-Equivalent Control Group Design. The research instruments applied are pre-tests and post-tests in the form of multiple choice questions. Data analysis was carried out through several tests, including normality tests, homogeneity tests, Independent sample T-Test t-tests, and N-Gain tests with the support of SPSS version 25. The collected data showed that the t-test produced a Sig. (2-tailed) value of 0.001 <0.05, so Ha was accepted and H0 was rejected. This is supported by the results of the N-Gain test, which showed an average score of 79.85 for the experimental group, equivalent to 80%, categorized as effective. This demonstrates that the deep learning approach impacts students' critical thinking skills in IPAS learning for Grade VI student at SD Negeri Laden 1 Pamekasan.